MODELO EVOLUTIVO DA PLATAFORMA DE ABROLHOS: DO PALEÓGENO AO NEÓGENO - Duarte, Romero Meyrelles (2020)
As part of the brazilian East Margin Continental Shelf, with distinct morphology from the continental shelf, the Abrolhos Shelf presents great ecological relevance, being the largest rhodoliths bank in the world and presenting the greatest south Atlantic